ANALISIS PENGARUH KEMUDAHAN PENGGUNAAN, KENYAMANAN, KEPERCAYAAN DAN KETERSEDIAAN FITUR TERHADAP MINAT NASABAH DALAM MENGGUNAKAN INTERNET BANKING KLIKBCA STUDI KASUS PADA NASABAH PT BANK CENTRAL ASIA TBK KANTOR CABANG PEMBANTU MASJID JAMIK TAHUN 2021 - Helen; Novika; Medinal (Jurnal Akuntansi Bisnis Dan Keuangan, 2022)
This study aims to analyze and obtain evidence on the influence of perceptions of ease of use, convenience, trust, and feature availability of intention to use internet banking KlikBCA. The results of this study are expected to contribute to the Bank in particular BCA in order to provide a service that is faster and easier for its customers. The object of this study is the BCA’s customers who use internet banking. Data used in this study are primary data, and data searching used questionnaires directly. The data used is primary data formed questionnaires that apply to BCA’s customers who use KlikBCA in Pangkalpinang amount is 100 respondents and using method probability sampling: simple random sampling. The results showed that perceptions of ease of use, convenience, trust, and feature availability have a positive and significant impact on interest in using internet banking.